Relationship of Total Oil Content and Planktonic Diatoms Abundance in the Coastal Waters of Lukit Kepulauan Meranti - Yuliani, Riza; Siregar, Sofyan Husein; Amin, Bintal (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This research was conducted in January 2024 in the waters of Lukit, Merbau District, Meranti Islands. This study aimed to analyze the total oil content and abundance of planktonic diatoms and determine the relationship between total oil content and abundance of planktonic diatoms. This study used a purposive sampling method. The sampling location was divided into three stations with three sampling points. Station 1 is in the oil company jetty area, Station 2 is in the crossing port area, and station 3 is far away from residential areas. The results of the analysis of total oil content was 0,252 ppm. The highest oil content was found at station 2, which was 0,274 ppm, and the lowest oil content was found at station 3, which was 0,222 ppm. The results of the planktonic diatom abundance ranged from 75 – 187,5 ind/L. The highest abundance was found at station 3, which was 166,67 ind/L, and the lowest was found at station 2, which was 79,17 ind/L. The results of the simple linear regression test obtained the equation y= 177,77-225,55x with the value of R² = 0,1321 and the correlation coefficient r = -0,36, which shows that higher total oil content will cause a decrease in the abundance of planktonic diatoms